El homo economicus: un análisis aplicado para el Perú - Huertas del Pino, Andrea (2007)
This paper examines the existence of the rational man paradigm on an empirical basis. It also analyzes whether there is a correlation between income levels of the sample and the results. It follows the same methodology applied by Daniel Kahneman, Amos Tversky and Ariel Rubinstein, using as subjects students of diverse socioeconomic strata with high and low income brackets. The results were further controlled by the level of education. The results show that the income level has an impact on the rationality of the responses through the perceptions of the level of risk involved. It has been found that the transitivity of the choices of the students depends on their socioeconomic milieu. This paper concludes that the level of consistency of people's behavior is positively correlated with their socioeconomic level. This conclusion opens up several other questions such as how rational is the low-income bracket decision to have children. As a result, we have to be cautious about surveys and other demonstrations of «popular preferences» which are often found to be inconsistent. Theories in favor of indirect decisions through representatives such as congressmen and the president of the republic are reinforced with this type of results.​